Association Agreement of European Union, as a particular form of internationalagreement - Butyter, Daniel (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2015)
In the modern foreign policy of the European Union association agreements are one of the key instruments of cooperation with third countries. Association Agreement provides legal framework for the cooperation with third countries. Association Agreements are prepared jointly by the authorities of the EU and the partner countries and vary depending on the partner. The purpose of this article is to determine the place of association agreementsamong other sources of law of European Union by presenting the evolution of these agreements in the EU foreign policy.
Keywords: European Union; Associatin Agreement; foreign policy of European Union